Patient perceptions of facilitators and barriers to reducing hazardous alcohol use among people living with HIV in East Africa - Lewis‑Kulzer, Jayne; Mburu, Margaret; Obatsa, Sarah; Cheruiyot, Julius; Kiprono, Lorna; Brown, Steve; Apaka, Cosmas; Koros, Hillary; Muyindike, Winnie; Kwobah, Edith Kamaru; Diero, Lameck; Aluda, Maurice; et al. (Substance Abuse Treatment, Prevention, and Policy, 2023)
Background: Hazardous alcohol use among people living with HIV is associated with poor outcomes and increased morbidity and mortality. Understanding the hazardous drinking experiences of people living with HIV is needed to reduce their alcohol use. Methods: We conducted 60 interviews among people living with HIV in East Africa with hazardous drinking histories. Interviews and Alcohol Use Disorder Identification Test (AUDIT) scores were conducted 41 – 60 months after their baseline assessment of alcohol use to identify facilitators and barriers to reduced alcohol use over time. Results: People living with HIV who stopped or reduced hazardous drinking were primarily motivated by their HIV condition and desire for longevity. Facilitators of reduced drinking included health care workers’ recommendations to reduce drinking (despite little counseling and no referrals) and social support. In those continuing to drink at hazardous levels, barriers to reduced drinking were stress, social environment, alcohol accessibility and alcohol dependency. Conclusions: Interventions that capacity-build professional and lay health care workers with the skills and resources to decrease problematic alcohol use, along with alcohol cessation in peer support structures, should be explored.
Keywords: HIV; Antiretroviral therapy; Alcohol; Adherence; East Africa